2019
DOI: 10.1149/2.1291908jes
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Highly Sensitive Voltammetric Determination of Citalopram with Glassy Carbon Electrode

Abstract: This work proposes a simple and very sensitive method for electrochemical determination of citalopram by differential pulse voltammetry (DPV) using glassy carbon electrode. The cyclic voltammetry measurements proved that citalopram undergoes irreversible, adsorption-controlled, two-electron oxidation process, accompanied by the release of two protons. The influence of different measurement conditions, such as type and pH of supporting electrolyte solution, as well as DPV parameters was investigated. The glassy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Ammonia, ammonium chloride, and sodium acetate were obtained from Merck (Germany). The phosphate, acetate, and ammonium buffer solutions were prepared as described in [ 9 ]. Glucose (Micropharm, Poland), hexadecyltrimethylammonium bromide, lactose, magnesium stearate, sodium dodecyl sulfate, starch, talc, titanium dioxide, and Triton X-100 (Sigma-Aldrich, USA) were used for interference studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ammonia, ammonium chloride, and sodium acetate were obtained from Merck (Germany). The phosphate, acetate, and ammonium buffer solutions were prepared as described in [ 9 ]. Glucose (Micropharm, Poland), hexadecyltrimethylammonium bromide, lactose, magnesium stearate, sodium dodecyl sulfate, starch, talc, titanium dioxide, and Triton X-100 (Sigma-Aldrich, USA) were used for interference studies.…”
Section: Methodsmentioning
confidence: 99%
“…The stock solution with expected CIT concentration of 1.250 mmol L −1 for each commercial medicament was prepared according to the procedure described in previous work [ 9 ]. For determination of CIT, 40.0 μL of selected stock solution was added to 10 mL of 0.1 mol L −1 PBS pH 7, and then measurements were conducted according to the standard addition calibration method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different analytical techniques were used to quantitatively determine CIT in aquatic samples. Among these methods are liquid chromatography (Sarıkaya et al 2021 ), gas chromatography (Behpour et al 2020 ), differential pulse voltammetry (Madej et al 2019 ), tandem mass spectrometry (Evans et al 2015 ) and capillary electrophoresis (Himmelsbach et al 2006 ). In order to avoid undesired accumulation of CIT in aquatic environments, different treatment methods were employed such as adsorption (Ek et al 2014 ; Guillossou et al 2019 ; Sharifabadi et al 2013 ), membrane bioreactor process (Arola et al 2017 ) and gamma radiation (Bojanowska-Czajka et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, their evident drawbacks, such as the need for complex and expensive instruments, the long analysis time, and the use of large volumes of toxic solvents have encouraged the scientific community to design new approaches for the detection of pharmaceuticals. While electrochemical methods have become an interesting alternative due to their simplicity, fast response, and low cost, only few studies based on these techniques have been reported to date for the determination of CTL [ 13 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%